Pengaruh Pemberian Back Exercise dan Slow-Stroke Back Massage Terhadap Penurunan Nyeri Haid Primer - Aryani, Ariska Nafiah, Wahyuni, S.Fis., M.Kes (2016)
Background: In general, when menstruation many women who feel the complaint of pain that lasts 2-3 days, starting the day before the start of menstruation. One of the ways and efforts to reduce back pain is with exercise and slow-stroke back massage. Back exercise to relaxing tense muscles that can open narrow blood flow so as to reduce the pain while the slow-stroke back massage can reduce pain and help reduce muscle tension. Objective: to know the different effects of back exercise and slow stroke back massage to the decline of the primary menstrual pain. Methods: This research is a quasi experimental research design pre and post test two group design. A sample of 30 students. This study was divided into 2 groups each group divided 15 students. The first group was given exercises back exercise 3 times a week with a duration of 20 minutes, each movement is given detention 8x count, then repeat the movement to relaxing and 2x reps. The second group was given treatment of slow stroke back massage with a duration of 20 minutes is given 3 times a week. Data analysis using paired samples t-test and independent sample t-test. Results: Test the effect in group I with a back exercise p value = 0.003 (p <0.005), while in group II with a slow stroke back massage p value = 0.000 (p <0.005). Different test results after treatment between groups I and II obtained value of p = 0.028. Conclusion: the provision of treatment of back exercise and slow-stroke back massage each influential in reducing menstrual pain, but the giving of slow stroke back massage better effect than giving back exercise.